Fully Homomorphic Encryption for Cloud Based E-Government Data - Rini Deviani; Sri Azizah Nazhifah; Aulia Syarif Aziz (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2022)
Cloud computing is a way of providing services, networks, hardware, storage, and interfaces for the construction of E-Government infrastructure that enables the delivery of services efficiently and achieves cost savings. Cloud services enable individuals and organizations to utilize cloud providers’ software and hardware resources stored remotely. The span between the client and the actual location of his data provides a barrier because this data can be obtained by a third party, risking the citizen’s data privacy. We examine a method based on the Fully Homomorphic Encryption (FHE) scheme in order to facilitate the processing of sensitive information pertaining to the E-Government that does not involve the disclosure of the original data. In this paper, we consider some general data operations to evaluate the feasibility of the FHE method and show that the accuracy are similar when data operations are applied to homomorphically encrypted data. The results of the experiment highlight the potential of the various privacy-preserving data operations that can be performed under FHE approach. These methods provide results that are equivalent to those achieved by unencrypted data and models within a decent amount of time.